2021
DOI: 10.1111/cura.12414
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Museum Experience Through the Lens of Instagram Posts

Abstract: The purpose of this study is to examine visitors' Instagram posts through a combination of quantitative methodology to cast light on museum experiences. To analyze a large quantity of Instagram data, we used computer vision and semantic analysis. The results of hashtag analysis showed that informative hashtags were the most prominent for all museums. It is notable that the geo-related hashtags such as exhibition venue and local information accounted for a significant portion of the total data. Little to no evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…The exhibition pieces themselves receive only marginal interest from visitors. Similar observations have been made by Rhee et al [57], where the clustering of photographs revealed that the museum's architectural features are more frequently photographed than the art itself in certain museums.…”
Section: Both the Exterior And The Interior Atrium Of The Depot Are P...supporting
confidence: 84%
See 1 more Smart Citation
“…The exhibition pieces themselves receive only marginal interest from visitors. Similar observations have been made by Rhee et al [57], where the clustering of photographs revealed that the museum's architectural features are more frequently photographed than the art itself in certain museums.…”
Section: Both the Exterior And The Interior Atrium Of The Depot Are P...supporting
confidence: 84%
“…In related research, photograph clustering has been used to identify the collective image of a destination based on social media content [31,56,57]. Clustering is commonly performed indirectly, through textual image labels given by the Cloud Vision API, which has been shown to produce inconsistent labels when noise is present in the photograph [58].…”
Section: Identifying Points Of Interest Via Photograph Clustering And...mentioning
confidence: 99%
“…Previous research studies have explored topics such as museum visitors' Instagram posts and placemaking (Budge, 2020), the interface between Instagram and museum objects (Budge & Burness, 2018), and how visitors communicate and share their museum and gallery visiting experiences on Instagram (Rhee et al., 2021; Suess & Barton, 2022; Villaespesa & Wowkowych, 2020; Weilenmann et al., 2013). These studies mainly focus on visitor‐generated Instagram posts or how museums go on to use or feature those contributions.…”
Section: Instagram's “Platform Vernacular”mentioning
confidence: 99%
“…Barasch, Zauberman, and Diehl (2018) argue that these museums have changed the way that visitors interact with artefacts as they immediately think in terms of photography when looking. This has been reflected in the changing policies of bricks-and-mortar museums, many of whom have relaxed their policies on taking photographs and encourage social media interaction by posting hashtags in the museum, introducing free Wi-Fi and holding photography competitions (Rhee, Pianzola, and Choi 2021). Individual artists have also recognised the potential of Instagram to exhibit their work.…”
Section: The Virtual Museum: Theories Trends and Developments Across ...mentioning
confidence: 99%